STUDI KOMPARATIF EFEKTIVITAS KOMUNIKASI MENGGUNAKAN E-LEARNING 4.0 DAN GOOGLE CLASSROOM SEBAGAI MEDIA PEMBELAJARAN JARAK JAUH DI UPN VETERAN JAKARTA PADA MASA COVID-19 - Chyntia Sucyati (2020)
The existence of Large Scale Social Restrictions (PSBB) due to the COVID-19 pandemic made most activities have to be done long distance, including in the education sector which eventually implemented distance learning (PJJ). The use of communication technology is increasingly relied upon for the achievement of learning objectives. Universitas Pembangunan Nasional (UPN) "Veteran" Jakarta as one of the campuses that applies PJJ also uses several learning media systems so that teaching and learning activities can continue even though there is limited space and time. This research is a comparative study of the effectiveness of communication E-learning 4.0 (E4.0) and Google Classroom as Distance Learning media (PJJ) at UPN Veteran Jakarta during the COVID-19 pandemic. This research was conducted to find out how much the comparative effectiveness of communication used in the PJJ process during the COVID-19 pandemic. Two media that will be compared in this study are E4.0, which is PJJ media owned and developed by UPN Veterans Jakarta, and Google Classroom, which is a Google feature that is also used to support learning. The theory used in this research is the new media theory. This research approach is quantitative with comparative research types. Researchers collected data by distributing questionnaires to pre-determined samples. The population in this study were students at UPN Veteran Jakarta class of 2019 and used stratified proportional random sampling technique to draw research samples. The results of the study see from the average dimensions of the value of effectiveness found that Google Classroom is higher than E4.0. After it is proved by the paired T test hypothesis the results of the Sig. 0.001 <0.05 so that Ho is rejected and Ha is accepted where there is a significant difference between the effectiveness of E40 and Google Classroom.